Prevalence of Hepatitis B and C in Patients of Thalassemia in Sargodha, Pakistan - Um-A-Aiman, Sadaf Liaqat, Bushra Aslam, Hussain Farooq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Thalassemia is one of the commonest genetic hematological disorders and a health issue of global concern. Because of repeated blood transfusions, ratio of hepatitis B and C positivity is escalating in these patients day by day who have further complicated the situation in the form of poor treatment outcomes and costs to individuals Aim: To measure the prevalence of hepatitis B and C among patients of thalassemia major in Sargodha, Pakistan. Study design: Cross-sectional study Place and duration of study: Rai Hospital & Hilal-e-Ahmar Hospital, Sargodha from 01-01-20221 to 31-12- 2021. Methodology: Three hundred and sixty thalassemia major patients, both beta and alpha, confirmed on hemoglobin electrophoresis admitted in the hospital were enrolled. Results: The mean age of the participants was 10.24±2.5 years, and 50% were male and 50% females. About 34% of the patients had hepatitis in which 30% had hepatitis C and 1.1% hepatitis B. 2.2% had both. Conclusion: Hepatitis b and C are highly prevalent among patients of thalassemia major. This also calls physicians, hematologists, pediatricians and policy makers to focus on counseling and support of thalassemia patients by providing them safe blood. Keywords: Prevalence, Hepatitis B and C, Thalassemia major, Blood transfusion